(untitled) (Global Journal of Medical Research, 2023)
Introduction When addressing the COVID-19 pandemic one must also address its remnants as well as the Long COVID-19 Syndrome or just Long COVID-19 which addresses a group of symptoms common to COVID but which persist even after the infectious picture has ended The main symptoms are fatigue dyspnea joint and muscle pain headaches and brain fog Other symptoms such as arrhythmias anxiety and sleep disorders have been described but the cause of these sequelae and the reason for them are not known for certain Methodology This is a literature review based on the SciELO and PubMed data platforms The search period was July 2023 meeting the inclusion criteria of articles from 2000 to 2023 in Portuguese and English online and in full text The following health descriptors DeCS were used as strategies to better evaluate the texts Long COVID syndrome COVID and Post COVID syndrome